Pharmacy OSCEs : a revision guide - Evans, Beti Wyn (Pharmaceutical Press, 2013)
Pharmacy OSCEs is the only pharmacy-specific OSCE revision guide. This easy-to-use book covers the key competencies that will be tested during your Objective Structured Clinical Examinations whether you are still studying or in practice.